2009
DOI: 10.1080/00343400802663532
|View full text |Cite
|
Sign up to set email alerts
|

What Attracts Human Capital? Understanding the Skill Composition of Interregional Job Matches in Germany

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 49 publications
6
60
0
Order By: Relevance
“…In line with many earlier studies (e.g. Arntz, 2010;Lawton et al, 2013), we find that job access has a positive effect on the neighbourhood selection of foreign highly skilled workers. The land value, tenure composition and the construction period of the dwellings in the neighbourhood have no significant effect on the inflow of these migrants at the 5 per cent level.…”
Section: Explaining the Initial Neighbourhood Choice Of Foreign Highlsupporting
confidence: 93%
“…In line with many earlier studies (e.g. Arntz, 2010;Lawton et al, 2013), we find that job access has a positive effect on the neighbourhood selection of foreign highly skilled workers. The land value, tenure composition and the construction period of the dwellings in the neighbourhood have no significant effect on the inflow of these migrants at the 5 per cent level.…”
Section: Explaining the Initial Neighbourhood Choice Of Foreign Highlsupporting
confidence: 93%
“…For seven different motives, participants in the MESARAS 2013 survey have been asked to state the maximum migratory move they would consider in order to realise the associated motive. In line with Arntz (2010), the results in Fig. 1 illustrate that especially economic motives might induce higher degrees of mobility.…”
Section: Migration Motives and Willingness To Movesupporting
confidence: 76%
“…; Ferguson et al. ; Storper and Scott ; Scott ; Arntz ). Some scholars also found that professional and managerial staff tended to move to ‘escalator regions’ such as South East England in pursuit of professional and personal development, especially at early stages of their career (Fielding ; Findlay et al.…”
Section: Skilled Internal Migration In Western Developed Countries Anmentioning
confidence: 99%
“…It has attracted extensive scholarly attention in developed countries (Findlay et al. ; Faggian and McCann ; Arntz ; Scott ). Studies of migration mechanism is commonly rooted in the classical assumptions that migrants are motivated by regional differentials in economic opportunities, and that, as an investment in human capital, people move to alternative locations to reap positive economic returns (Sjaastad ; Todaro ; Greenwood ).…”
Section: Skilled Internal Migration In Western Developed Countries Anmentioning
confidence: 99%